Ely Cathedral
The Lady Chapel, had been started the year before the tower fell. Its building was structural triumph, for it has the widest stone-vaulted spam of any English religion building. In achieving this, the adoption of the lighter lierne vaulting was a major contributory factor. all the walls of the chapel which has been robbed of its statuary by reformers, were decorated with niches and arcading of the most intricate and decorative sort, turning, as it were, an Early English cathedral west front inside out.